Recycling equipment and technology for municipal solid waste : material recovery facilities - Swartzbaugh, Joseph (Noyes Data Corp., 1993)
This technology transfer handbook describes recycling equipment and technology for municipal solid waste (MSW) at material recovery facilities (MRFs). It points out what technically can be done, what material specifications can be achieved, and what the different manual and mechanical material separation and recovery approaches can cost. It is intended to give guidance as to what should be incorporated into startup, implementation, and acceptance testing of any equipment and systems to be included in the MRF.
Keywords: Recycling (Waste, etc.) -- Handbooks, manuals, etc.; elektronické knihy; electronic books